Antimony-doped tin oxide embedding graphene-based aerogel for infrared barriering. Issue 6 (15th April 2019) - Li, Hongyan; Song, Limeng; Liu, Hongli; Li, Jiyuan; Yang, Aiwu; Sun, Cong; Li, Ruyi; Fu, Yongqiang; Yu, Chaorun
Abstract: A hybrid three-dimensional network structure was composed by the electrostatic-driven self-assembly via sol-gel method, which contained antimony-doped tin oxide (ATO) particles and graphene oxide aerogel (GOA). Absorbing and scattering near-infrared light composite of reduced graphene oxide aerogel/antimony-doped tin oxide (rGOA/ATO) was obtained by subsequent CO2 supercritical drying and calcination treatment in flowing nitrogen. Characterization of the as-prepared samples were performed by scanning electron microscopy (SEM), fourier transform infrared (FT-IR) spectroscopy, thermogravimetric analysis (TGA), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, nitrogen adsorption-desorption, ultraviolet visible near infrared spectroscopy (UV–VIS–NIR) and compressive stress. The radiation attenuation characteristics of composite materials were investigated in the near-infrared range at room temperature. The results showed that the ATO particles were well dispersed onto graphene oxide (GO) sheets, leading to the enhanced absorbing and scattering performance of radiative near-infrared. Consequently, the prepared rGOA/ATO hybrid materials showed the excellent radiation infrared barriering properties.